Acute deep brain stimulation of the paraventricular nucleus of the hypothalamus increases brown adipose tissue thermogenesis in rats. (16th March 2023) - Mota, Clarissa M.D.; Siler, Dominic A.; Burchiel, Kim J.; Madden, Christopher J.
Highlights: Deep brain stimulation (DBS) of the PVN increases brown adipose tissue (BAT) thermogenesis. Blockade of local GABAA receptors prevents the increases of BAT thermogenesis by DBS of the PVN. DBS of the rostral raphe pallidus area (rRPa) inhibits brown adipose tissue thermogenesis. Blockade of local GABAA receptors prevents the inhibition of BAT thermogenesis by DBS of the rRPa. Abstract: Brown adipose tissue (BAT) activity is controlled by the sympathetic nervous system. Activation of BAT has shown significant promise in preclinical studies to elicit weight loss. Since the hypothalamic paraventricular nucleus (PVN) contributes to the regulation of BAT thermogenic activity, we sought to determine the effects of electrical stimulation of the PVN as a model of deep brain stimulation (DBS) for increasing BAT sympathetic nerve activity (SNA). The rostral raphe pallidus area (rRPa) was also chosen as a target for DBS since it contains the sympathetic premotor neurons for BAT. Electrical stimulation (100 µA, 100 µs, 100 Hz, for 5 min at a 50 % duty cycle) of the PVN increased BAT SNA and BAT thermogenesis. These effects were prevented by a local nanoinjection of bicuculline, a GABAA receptor antagonist. We suggest that electrical stimulation of the PVN elicited local release of GABA, which inhibited BAT sympathoinhibitory neurons in PVN, thereby releasing a restraint on BAT SNA. Electrical stimulation of the rRPa inhibited BAT thermogenesis and this was prevented by a local nanoinjection of bicuculline, suggesting that local release of GABA suppressed BAT SNA. Electrical stimulation of the PVN activates BAT metabolism via a mechanism that may include activation of local GABAA receptors. These findings contribute to our understanding of the mechanisms underlying the effects of DBS in the regulation of fat metabolism and provide a foundation for further DBS studies targeting hypothalamic circuits regulating BAT thermogenesis as a therapy for obesity.